Trauma and the content of hallucinations and post‐traumatic intrusions in first‐episode psychosis. (10th March 2020) - Peach, Natalie; Alvarez‐Jimenez, Mario; Cropper, Simon J.; Sun, Pamela; Halpin, Emma; O'Connell, Jessica; Bendall, Sarah
Abstract : Objective: Increasing evidence suggests experiences of childhood trauma may be causally related to the development of hallucinations. Cognitive theories of psychosis suggest post‐traumatic intrusions to be a primary mechanism in this relationship. These theories predict that the content of hallucinations will be related to traumatic experiences; however, few studies have investigated this. This study examined the relationship between childhood trauma, the content of hallucinations, and the content of post‐traumatic intrusions in a sample with first‐episode psychosis. Methods: Sixty‐six young people aged 15–25 experiencing a first episode of psychosis were recruited from an early intervention service. Participants completed assessments of traumatic experiences, hallucination content, and post‐traumatic intrusion content using a systematic coding frame. The coding frame assessed for three types of relationships between traumatic experiences, the content of hallucinations, and the content of post‐traumatic intrusions: direct relationships (hallucination content exactly matching the trauma/intrusion), thematic relationships (hallucinations with the same themes as the trauma/intrusion), and no relationship (hallucination and trauma/intrusion content unrelated). Results: Of those people who reported trauma and hallucinations ( n = 36), 22 of these (61%) experienced post‐traumatic intrusions, and of these, 16 (73%) experienced hallucinations that were directly or thematically related to their post‐traumatic intrusions. Twelve people experienced hallucination content directly related to their trauma, six of whom (50%) also had intrusions relating to the same traumatic event as their hallucinations. Conclusions: The finding that some people experience hallucinations and post‐traumatic intrusions relating to the same traumatic event supports theories proposing a continuum of memory intrusion fragmentation. These results indicate that early intervention services for young people with psychosis should provide assessment and intervention for trauma and PTSD and should consider the impact of past traumatic events on the content of current hallucinatory experience. Practitioner points: Trauma and post‐traumatic stress disorder should be assessed in those experiencing a first episode of psychosis. Interventions for trauma should be offered in early intervention for psychosis services. In a notable proportion of people, hallucination content is related to traumatic experiences. Clinical assessment and formulation of hallucinations requires consideration of how past traumatic events may be contributing to hallucinatory experience. It is important for clinicians to have an understanding of the phenomenological differences between hallucinations and post‐traumatic intrusions when conducting clinical assessments with people with comorbid psychosis and PTSD.